The effectiveness of teacher focused feedback (form or content) on the quality of the students' essays among the form two students of Sekolah Menengah Kebangsaan Tengku Intan Zaharah, Dungun, Terengganu Darul Iman / Ahmad Mohd Ali - Mohd Ali, Ahmad (2002)
Teachers have been spending much of their time dealing with the students and their writing capabilities especially essay writing. Among the approaches used by the teachers in managing the writing lessons are form-focused and content - focused feedback where the students are provided with the respective feedback, either on forms or contents. Twenty Form 2 students of Sekolah Menengah Kebangsaan Tengku Intan Zaharah, Dungun, Terengganu participated in the study. One of the English teachers of the school also participated in the study. Presently, he taught them writing compositions. In the study, the students were required to write four compositions. They were divided into four groups and given different types of feedback The different types of feedback were form feedback, content feedback, both form and content feedback and no feedback Their mean scores for their first and final compositions were calculated, analyzed and compared to find out the effect of their respective feedback. Among the findings of this study was that focused feedback have brought about improvement in students’ writings An interesting finding was that, the students’ writing performances improved regardless of any feedback given to them. However this study showed that the level of improvement did depend on a few factors including the types of feedback the syudents received. Therefore, this study was aimed at giving teachers guidelines on the types of feedback that they could apply when dealing with their students’ writing activities. Their skills and knowledge in providing the suitable response to students’ writing would enhance their students’ writing progress and their motivation to write better composition.